Immunization in Developing Countries : Its Political and Organizational Determinants - Gauri, Varun; Khaleghian, Peyvand (World Bank, Washington, DC, 2013)
The authors use cross-national social, political, economic, and institutional data to explain why some countries have stronger immunization programs than others, as measured by diphtheria-tetanus-pertussis (DTP) and measles vaccine coverage rates and the adoption of the hepatitis B vaccine. After reveiwing the existing literature on demand- and supply-side side factors that affect immunization programs, the authors find that the elements that most affect immunization programs in low- and middle-income countries involve broad changes in the global policy environment and contact with international agencies. Democracies tend to have lower coverage rates than autocracies, perhaps because bureaucratic elites have an affinity for immunization programs and are granted more autonomy in autocracies, althought this effect is not visible in low-income countries. The authors also find that the quality of a nation's institutions and its level of development are strongly related to immunization rate coverage and vaccine adoption, and that coverage rates are in general more a function of supply-side than demand effects. there is no evidence that epidemics or polio eradication campaigns affect immunization rates one way or another, or that average immunization rates increase following outbreaks of diphtheria, pertussis, or measles.